Balanced Choices: Examining the Impact of Dietary Diversity on BMI, Health Risks, and Rising Rates of Obesity in Kenya - Lilian Korir; Dennis Sedem Ehiakpor; Gideon Danso-Abbeam; Justice Gameli Djokoto; Marian Rizov (Obesities, 2024)
The study examines the link between dietary diversity and BMI using data from Kenyan women aged 15–49. By exploring how dietary diversity affects BMI across various BMI categories, the study examines the demand for diet diversity and its impact on BMI. The results reveal a positive relationship between food diversity and BMI at all quantiles, suggesting that a more varied diet is associated with increased BMI levels among underweight, overweight, and obese individuals. This indicates that the correlation between dietary diversity and health outcomes in higher BMI categories may be `unfavourable', with increased food diversity linked to a higher risk of `unfavourable' BMI categories, i.e., overweight and obesity. This may be attributed to higher caloric intake and/or higher consumption of saturated fats and cholesterol from a more diverse diet, which can contribute to increased BMI. These findings highlight the need to consider moderation and balance in energy intake and the overall nutritional quality of diets when considering and evaluating diets and dietary diversity and in formulating and shaping food policies.
Keywords: 330; diet quality assessment; healthy food diversity score; diet diversity score; diverse diet demand; Kenya